2009
DOI: 10.1007/s00421-008-0965-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the leg muscle pump on the rise in muscle perfusion during muscle work in humans

Abstract: The transient and steady-state effects of the calf muscle pump on the rise in muscle perfusion during rhythmic plantarflexions were investigated in 20 volunteers. Because a large hydrostatic column would increase the effect of a muscle pump, exercise in the supine and head-up tilted positions was compared. Within approximately 15 s of the start of muscle work, femoral artery flow (ultrasound Doppler) rose 0.37 L/min above rest in the supine and 0.5 L/min above rest in the tilted position. The latter is a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 35 publications
(104 reference statements)
3
38
1
Order By: Relevance
“…The rationale for this study was that the primary evidence for a muscle pump effect in exercise hyperemia comes from results of experiments which have demonstrated that limb position influences the blood flow response to muscle contraction (12,22,25,31,36). We reasoned that a critical control experiment has been lacking, i.e., testing whether the response to vascular challenges other than contraction elicit positional differences in blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The rationale for this study was that the primary evidence for a muscle pump effect in exercise hyperemia comes from results of experiments which have demonstrated that limb position influences the blood flow response to muscle contraction (12,22,25,31,36). We reasoned that a critical control experiment has been lacking, i.e., testing whether the response to vascular challenges other than contraction elicit positional differences in blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Because of technical limitations, it has not been feasible to perform experiments to directly test this hypothesis, yet the idea has persisted despite the lack of direct confirmation. Data from studies showing a greater blood flow response to muscle contractions when the limb is in the dependent position (12,22,25,31,36) have been the primary evidence for a skeletal muscle pump contribution to exercise hyperemia. We have argued previously that the magnitude of contraction-elicited changes in blood flow is far greater than can be accounted for by putative changes in intravascular pressure (38) and that the time course of changes in blood flow does not correlate with that predicted from the muscle pump (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not noted by Purslow is another function of this layer: these normal pressure changes result in cyclical changes throughout the gait cycle, which assists in venous return of blood to the heart, with the calf muscles serving as a "second heart pump" (18,19) and assisting with perfusion to the muscle itself. (20) Furthermore, the arteriolar dilation previously noted by Hocking (10) may further contribute to this muscle pumping mechanism.…”
Section: International Journal Of Therapeutic Massage and Bodywork-vomentioning
confidence: 91%